Parent’s Technology Acceptance Using TAM Toward Their Purchase Intention on Augmented Reality Educational Product (Journal of Innovation, Business and Entrepreneurship, 2020)
Augmented reality (AR) is a concept that fuse virtual and reality perspective that have various possibilities of implementation. With the AR technology, end user could enhance their experience and interaction toward the material that deliver by AR technology. One of the common implementations of AR is in the educational sector. Research found that AR could bring immersive experience and brings communal interaction at the same time which mean the implementation of AR in educational sector is a great addition for learning method. However, the augmented reality technology still considers as a new technology and the implementation of the technology not fully aware by entire potential customer. With the rise amount of augmented reality enabler company, as a fundamental the company should know how the technology is accepted by the current stage of the market and how their intention to purchase the product afterward especially in educational sector that the one that have financial capability is not the end user or children but the parent. Therefore, the research is exploring (1) how is the technology acceptance of augmented reality product in parent perspective (2) what is the significant factor of the technology acceptance for parents toward augmented reality educational product (3) what is the relation of technology acceptance of augmented reality educational product in parent’s perspective with their purchase intention (4) how to design technology acceptance strategy that affect purchase intention for augmented reality educational product. Spread to 100 respondents with quantitative methodology that aim parent with kids enroll in school as the target research respondent. In order to get the result, the research using descriptive analysis, simple linear regression and multiple linear regression methodology from parent respondent. The research show that there is actual relation between TAM (perceived usefulness, perceived ease of use and perceived enjoyment) and parent purchase intention. From the finding, perceived enjoyment become the most contributor dimension toward parent purchase intention as the parent intent to have fun factor from the AR educational product usage. In brief, the research would be beneficial for company that runs in AR industry in order to penetrate educational sector by developing strategy from the research result.Keywords: Augmented Reality, Technology Acceptance Model, Purchase Intention, Educational Product, Descriptive Analysis